STELARR Volume II—Central Asia and Middle East: Opportunities for rangelands restoration through livestock value chains - Dhehibi, Boubaker; Oumer, A.; Souissi, Asma (International Livestock Research Institute, 2025)
This overview outlines potential investment opportunities in rangeland rehabilitation in the Central Asia and Middle East region, based on the framework developed by Baker (2024). The assessment examined three value chains: cashmere, camels, and minerals, oil and gas. The cashmere value chain encompasses China, Mongolia and Pakistan, focusing on the production and application of cashmere. The camel value chain, centred in Saudi Arabia, targets meat, milk and racing. Lastly, the minerals, oil, and gas value chain focuses on countries within the Gulf Cooperation Council, particularly Saudi Arabia.